1991
DOI: 10.2172/10179749
|View full text |Cite
|
Sign up to set email alerts
|

Office equipment energy use and trends

Abstract: Lawrence Berkeley Laboratory is an equal opportunity employer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…In the past two decades, energy used by personal computers (PCs) has grown dramatically, rising from essentially zero to an estimated 10 billion kWh in the United States as of 1993 (60, 61).7 The average desktop PC with a cathode ray tube (CRT) screen draws about 135 watts while on (61). However, research on patterns of PC use by the Canadian National Research Council found that PCs are actively in use (measured by keyboard or mouse activity) between 30% and 40% of the time, and that about 20% of machines are left on all night (62).…”
Section: Personal Computersmentioning
confidence: 99%
“…In the past two decades, energy used by personal computers (PCs) has grown dramatically, rising from essentially zero to an estimated 10 billion kWh in the United States as of 1993 (60, 61).7 The average desktop PC with a cathode ray tube (CRT) screen draws about 135 watts while on (61). However, research on patterns of PC use by the Canadian National Research Council found that PCs are actively in use (measured by keyboard or mouse activity) between 30% and 40% of the time, and that about 20% of machines are left on all night (62).…”
Section: Personal Computersmentioning
confidence: 99%
“…Saturations for the other end uses are either 100% (for electric indoor lighting, outdoor lighting, and miscellaneous) or are already accounted for in the estimation process (for heating and all non-electric end uses, see above). The importance of the office equipment end use _cd to CIEE sponsorship (with CEC and PG&E funding) of a detailed examination of office equipment energy use trends in the PG&E service territory by LBL (Piette, et. al.…”
Section: Accounting For Fuel Saturation Effectsmentioning
confidence: 99%
“…As a result, various research on practical strategies for managing energy supply and demand have been performed [10][11][12]. Office equipment is now thought to be the end-use of electrical energy in the commercial sector which is rising at the highest [13].…”
Section: Introductionmentioning
confidence: 99%